Strategic inertia in top management teams: causes and combined effects - Perini, Luis Fernando (2021)
This study investigates the phenomenon of inertia in organizations, especially what is conceptualized as strategic inertia, that is inertia affecting a firm’s top management teams (TMT). The study is composed of three articles that dialogue with each other. In the first article we perform a systematic literature review of the different terms, definitions, and level of analysis the management field used to characterize the inertia construct, examine the multiple causes of inertia in organizations, and cluster them into six different groups of causes. In the second article we delve into the causes of strategic inertia affecting top management teams and individuals and suggest an integrated analysis of the interplay of these drivers, which have frequently been investigated separately. A tentative model of their interaction is advanced. The third article presents an empirical study that addresses the reasons for the adaptation and inertia of two companies operating in the fast-moving consumer goods (FMCG) industry. The results indicate that the pre-selected drivers of strategic inertia influenced the responses of both organizations, as well as other causes not previously considered. Strategic inertia is a complex phenomenon with multiple causes. The final section of this article discusses how some of the findings can be used by practitioners to support their organizations’ adaptative capacity. The accelerating pace of changes in industries and markets demand that top managers continuously adapt and innovate their organizations.